National Amil Zakat Agency as a Moderation of Perception and Religion on the Decision to Pay Zakat - Hardana, Ali; Nasution, Jafar; Damisa, Arti (Dirham: Journal of Sharia Finance and Economics, 2025)
Purpose: The purpose of this study is to identify the variables that affect muzakis' zakat payment decisions at the National Amil Zakat Agency. Altruism was included in this study as a moderating variable as well. Muzaki's capacity to decide to pay zakat is a result of his attention to and awareness of doing so. Muzaki may decide to distribute zakat at the National Amil Zakat Agency (BAZNAS). Methodology/approach: The population in this study is the entire community in Indonesia, with purposive sampling used to select specific respondents. The sample size was determined using the "ten times the number of formative indicators" method, resulting in 230 respondents. Data was collected through online questionnaires distributed to millennials in Indonesia via Google Forms. The analysis was conducted using Warp PLS 6.0, which involved three stages: 1) Evaluation of the Measurement Model, 2) Evaluation of the Structural Model, and 3) Hypothesis Testing. Results/findings: Then the variables of perception and religiosity have no significant effect on the muzaki's decision to pay zakat to the National Amil Zakat Agency through altruism. The results of this study are expected to be useful for related parties, especially the National Amil Zakat Agency, to continue to improve and maintain the factors that influence Muzaki's decisions in carrying out Zakat payments. Conclusion: This study finds that perception and religiosity significantly influence muzaki's decision to pay zakat through BAZNAS, while altruism does not have a significant moderating effect. These results suggest that BAZNAS should focus on enhancing public awareness of zakat's spiritual and social benefits. Limitation: The study's sample is limited to millennials in Indonesia, which may not fully represent the general population. The use of purposive sampling and online surveys could introduce bias, and the insignificance of altruism requires further exploration in future studies. Contribution: This research contributes to understanding zakat payment behavior by emphasizing the importance of perception and religiosity. It offers practical insights for BAZNAS to improve zakat collection and enhance poverty alleviation efforts.